SDD22 Broad-gauge Diesel Locomotive Exported to Pakistan - SHANG Qin; LI Gang; PENG Changfu; QIU Jianjun (机车电传动)
The general arrangement, main technical parameters and performance of SDD22 AC/DC electric drive broad-gauge diesel locomotive exported to Pakistan were introduced, focusing on the composition and working principle of the engine, electrical system, car body and bogie, brake system and auxiliary system. The main difficult points, countermeasures, main characteristics and innovation of the locomotive were analyzed. The locomotive could satisfy the requirement of 1676mm broad-gauge and high-temperature more-sandstorm operation environment such as India, Argentina etc, and with replacing of 1520mm broad-gauge, standard gauge or meter-gauge bogie, the locomotive could also extended to Middle Asia, Africa, South America etc.